The On-Freezing Phenomenon: Cognitive and Behavioral Aspects - Rita Moretti; Paola Torre; Rodolfo M. Antonello; Francesca Esposito; Giuseppe Bellini (Parkinson's Disease)
Freezing of gait is a warning sign of Parkinson's disease. One could distinguish off-freezing, which is associated with dopaminergic therapy and to its titration, and it is clinically related to wearing-off phenomenon. Differently, the on-freezing phenomenon seems to be related to a neural disruption of the frontal-parietal-basal ganglia-pontine projections; clinically, it does not respond to therapy modifications or to different drug titration. In a group of patients with on-freezing, we have detected an alteration of focusing attention, an impairment of set-shifting, in addition to poor abstract reasoning and a reduction of planning. These aspects have been even more evident, when compared with the results obtained by a group of PD patients, without freezing.